Conexões entre cultura popular e cultura acadêmica: recontextualização curricular na prática de pesquisa jurídica do curso de Direito da Anhanguera Educacional/Faculdade Atlântico Sul em Pelotas - Henning, Ana Clara Corrêa (2008)
This thesis follows Curricular Research, Professionalization and Teaching Studies, and is based on investigation of Cultural Studies, Basil Bernstein s analyses on classification and framing, Boaventura de Souza Santos interpretation of the paradigmatic transition of contemporary science, as well as Max Horkheimer s and Theodor Adorno s analyses on the dual relationship between instrumental and emancipative reason. The teacher s proposal of curricular recontextualization of legal practice and research encompassing theoretical, jurisprudential and field research was performed by three professors and was put into practice by twenty-one undergraduate students attending the first and second terms of the Law Course at Anhanguera Educational/Atlântico Sul College in Pelotas, Rio Grande do Sul, from March to December 2007 and, in two specific cases, up to the beginning of 2008. The activities included curricular components of Legal Science Methodology, Legal Anthropology and Legal Sociology. The pedagogic practice aimed to build emancipative and critical knowledge by means of interdisciplinary and multicultural research that was able to connect academic legal knowledge to the popular and practical lore of groups and local communities, eventually providing students with a broader, more inclusive view of law. For such it intended to modify the traditional pedagogic code of Law Courses, which is based on the Positivist Theory, by investing on flexibility of power and social control, being guided by the characteristics of the emerging paradigm according to the theorization used in the initial proposal. A case study of qualitative approach was performed by means of semistructured interviews whose results confirmed the possibility of inverting the poles of western rationality, however small, and that of building emancipative knowledge directed towards the autonomy of thought in students, the critical analysis of state law, and the addition of other legal rules, prepared and applied by local communities.